Early Detection of Bilateral Testicular Metastases From Prostatic Adenocarcinoma Using 68Ga-PSMA Ligand PET/CT. (July 2017) - Weiberg, Desiree; Radner, Herbert; Derlin, Thorsten; Thon, Walter F.
Abstract : Abstract: We present the case of a 76-year-old man with biochemical relapse after primary therapy for prostate cancer. 68 Ga prostate-specific membrane antigen (PSMA) ligand PET/CT performed for localization of recurrent disease revealed bilateral metastases to the testes. Histopathologic evaluation after bilateral orchiectomy revealed testicular metastases. Metastases to the testes are rare and usually seen in advanced stages. 68 Ga-PSMA ligand PET/CT is a highly sensitive and specific imaging method for the detection of primary and metastatic prostate cancer and has refined diagnostic approaches. This case highlights the potential of PSMA-targeted PET/CT for detection of prostate cancer metastases, even in very unusual localizations.